2016
DOI: 10.1038/srep33427
|View full text |Cite
|
Sign up to set email alerts
|

BMS-708163 and Nilotinib restore synaptic dysfunction in human embryonic stem cell-derived Alzheimer’s disease models

Abstract: Alzheimer’s disease (AD) is the most common form of dementia. Cellular AD models derived from human pluripotent stem cells are promising tools in AD research. We recently developed human embryonic stem cell-derived AD models which overexpress mutant Presenilin1 genes, and which exhibit AD phenotypes, including synaptic dysfunction. In this study, we found that our AD models showed reduced levels of RAB3A and SV2B proteins in the pre-synapses, which is a possible cause of electrophysiological abnormalities. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…SV2B KO mice subjected to toxic species of amyloid-β protein are protected from both memory decline and decrease in CHAT activity in the hippocampus [10], opening up the possibility that SV2B is needed to regulate CHAT. Furthermore, reduced SV2B expression has also been found in other neurodegenerative diseases connected to acetylcholine [56][57][58]. The co-regulation between SV2B and CHAT in the neuroblastoma cell lines used here indicates that interconnectivity exists between SV2B and CHAT even outside of disease models where SV2B is missing, or due to failure in cholinergic neurons.…”
Section: Discussionsupporting
confidence: 56%
“…SV2B KO mice subjected to toxic species of amyloid-β protein are protected from both memory decline and decrease in CHAT activity in the hippocampus [10], opening up the possibility that SV2B is needed to regulate CHAT. Furthermore, reduced SV2B expression has also been found in other neurodegenerative diseases connected to acetylcholine [56][57][58]. The co-regulation between SV2B and CHAT in the neuroblastoma cell lines used here indicates that interconnectivity exists between SV2B and CHAT even outside of disease models where SV2B is missing, or due to failure in cholinergic neurons.…”
Section: Discussionsupporting
confidence: 56%
“…Tyrosine kinase inhibitors have an anti-inflammatory effect through modulation of various markers of neuroinflammation in animal models [ 40 , 41 ]. Nilotinib was associated with rescued synaptic dysfunction [ 46 ]. Both nilotinib and bosutinib were found to prevent cell death due to trans-activating response of DNA/RNA-binding protein (TDP)-43 pathology, but only nilotinib reversed mitochondrial impairment [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a mouse model of AD, nilotinib decreases Aβ-plaque-induced increases in proinflammatory cytokine levels in the hippocampus, and in patients with AD or PD, nilotinib improves learning/memory behavior [ 12 14 , 23 ]. Nilotinib significantly restores synaptic function in human cellular AD models by increasing the levels of the synaptic proteins Rab3A and SV2B [ 55 ]. Six months of treatment with nilotinib (150 mg and 300 mg) improves cognition in patients with Parkinson’s disease compared to baseline [ 13 ], whereas Cludiani et al reported that leukemia patients treated with nilotinib experience memory dysfunction 4–6 months after cessation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%